Caracterização de lesões desportivas no basquetebol - Almeida Neto, Antônio Francisco De [UNESP]; Tonin, Juliana Petrongari [UNESP]; Navega, Marcelo Tavella [UNESP] (Pontifícia Universidade Católica do Paraná (PUC-PR), 2013)
INTRODUCTION: Basketball is characterized with high injury rate. In the literature it's not defined whether or not there are differences between the sexes. OBJECTIVE: Characterize and analyze the incidence of athletic injuries in basketball players, comparing the sexes. MATERIALS AND METHODS: Fifteen under-23 category athletes of each sex were interviewed with the reported morbidity inquire. RESULTS: The age of the female and male teams, in average, was 18 ± 0.65 and 18.20 ± 1.57 years respectively. The male team had more injuries than the female one (respectively 2.6 ± 1.45 against 1.2 ± 1.18, p < 0.05). The joint damage was the most common injury in the male team, representing 58.97%, and the second most common in the female team (33.33%). The lower limbs were the most common injured sites (80.95% in the female and 69.23% in the male). The most frequent injury mechanism in the male team was the landing (43.59%), and in the female was the vertical jump (28.57%). In both teams the most injuries occurred during the training (61.9% in the female and 71.8% in the male). The absence was necessary in 47.62% (female) and 56.41% (male). Great part of the athletes didn't received any treatment (61.9% and 51.28% in the female and male team respectively). The return to the activities was mostly symptomatic, in both female and male team (85.71% and 84.62% respectively). CONCLUSION: The incidence of injuries in basketball is higher in the lower limbs. The male team is more likely to suffer injuries, and the main injury mechanisms were different between male and female team.

INTRODUÇÃO: O basquete apresenta altos índices de lesão. Na literatura ainda não se definiu existem ou não diferenças entre os sexos. OBJETIVO: Caracterizar e analisar a incidência de lesões desportivas em atletas de basquetebol, com comparação entre os sexos. MATERIAIS E MÉTODOS: Quinze atletas de cada sexo, da categoria sub-23, foram entrevistados com o inquérito de morbidade referida. RESULTADOS: A média de idade das equipes feminina e masculina foi de 18 ± 0,65 e 18,20 ± 1,57 anos, respectivamente. A equipe masculina apresentou mais lesões que a feminina (2,6 ± 1,45 contra 1,2 ± 1,18 respectivamente, p < 0,05). A lesão articular foi o tipo de lesão mais comum na equipe masculina, representando 58,97%, e o segundo mais comum na feminina (33,33%). Os membros inferiores foram a região mais acometida por lesões (80,95% na feminina e 69,23% na masculina). O mecanismo de lesão mais comum na equipe masculina foi a aterrissagem (43,59%) e na feminina o salto vertical (28,57%). Em ambas as equipes, a maior parte das lesões ocorreu durante os treinos (61,9% na feminina e 71,8% na masculina). Foi necessário o afastamento em 47,62% (feminina) e 56,41% (masculina). A maioria dos atletas não realizou tratamento (61,9% e 51,28% feminino e masculino, respectivamente). O retorno às atividades, na maioria das vezes, foi sintomático, tanto na equipe feminina quanto na masculina (85,71% e 84,62% respectivamente). CONCLUSÃO: A incidência de lesões no basquetebol é maior nos membros inferiores. A equipe masculina mostra-se mais propensa a sofrer lesões, e os principais mecanismos de lesão foram diferentes entre as equipes masculina e feminina.
Characterization of sport injuries in the basketball
Keywords: Lesões esportivas; Basquetebol; Fisioterapia (especialidade); Athletic injuries; Basketball; Physical therapy (specialty)